A REVIEW OF OPERATIONS IN PEDIATRIC NASAL DISORDERS - Yamamoto, Kunio; Ishizuka, Yoich; Terashima, Kunio; Koizumi, Tatsuro (JIBI INKOKA TEMBO, 1996)
We have often encoutered pediatric nasal disorders in routine clinical examinations. Therefore, in this study we report cases in which we performed operations for pediatric nasal disorders, mainly sinusitis. We have included clinical discussions that cover nasal disorders, X-ray diagnosis, age, techniques used, postoperative results. The subjects in this report consisted of 145 cases (79 boys and 63 girls), all experiencing pediatric nasal disorders. Their ages ranged from 5 to 16. The operations were performed from 1985 to 1994. In regard to the number of cases by age, the peak age was 15 showing that nasal disorders increase with age. Ages 11 and older accounted for 90% of the cases. In regard to the number of cases per year, there has been a decline since 1992. A study on the long term prognosis by means of a questionnaire revealed the complete recovery rate to be 46.3%. For pediatric nasal disorders, there may be a need to consider patients age and growth rate when deciding on the type of operation or techniques to be employed.